Organization and education among Salvadoran political prisoners - Hammond, John L. (Crime, law and social change, 1996)
During twelve years of war, the Salvadoran government imprisoned thousands of activists. Confronting massive violations of their human rights, prisoners struggled against prison authorities to resist the abuses to which they were subjected. They also educated themselves mutually, applying the principles of popular education widespread in the Salvadoran popular movement, which emphasized close integration between pedagogy and politics both in the content of education and in the political process. In opposing oppressive confinement and in mutually educating themselves, prisoners continued the political struggle they had been waging outside. Human rights movements working to protect them against violations of their rights used a rhetoric which presented them as helpless victims, but the prisoners' own testimonies reveal that they were active protagonists opposing injustice even in prison.